Fulfillment of Legal Certainty for Government Employees with Employment Agreements as State Civil Apparatus - Sugiyanto Sugiyanto; Bha'iq Roza Rakhmatullah; Erwin Aditya Pratama (Kosmik Hukum, 2025)
The principle of the rule of law is explicitly stated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, emphasizing the need for legal certainty, justice, and protection for all citizens, including Government Employees with Employment Agreements (PPPK) as part of the State Civil Apparatus (ASN). National development relies on the role of ASN, which includes both Civil Servants (PNS) and PPPK. However, despite carrying out equivalent duties and responsibilities, PPPK often face uncertainty regarding the continuity of their employment status. This research aims to analyze why PPPK, as State Civil Apparatus, are not yet guaranteed continued employment and how legal certainty can be fulfilled for them. The study employs an empirical juridical approach, utilizing descriptive-analytical methods through interviews, document studies, and observations. The findings reveal that the absence of guaranteed continued employment for PPPK stems from weaknesses in the normative framework, particularly the State Civil Apparatus Law, which does not adequately regulate employment continuity, rights, and obligations of PPPK. Additionally, institutional inconsistencies and a legal culture that differentiates PPPK from PNS contribute to the problem. To address these issues, legal reform is needed in terms of legal substance, legal structure, and legal culture to create a more comprehensive and equitable regulatory system. Such reform must align with the values of Pancasila and the 1945 Constitution, ensuring legal certainty and fair treatment for all components of the State Civil Apparatus, including PPPK. This research underscores the urgency of regulatory revisions to uphold justice and professional security for PPPK.